Assessment of serum ceruloplasmin levels in chronic Periodontitis patients with type ii diabetes mellitus - SARVODAYA VAISHNAVI RATHEESH,; SANGEETHA SUBRAMANIAN,; DAYANAND JOHN VICTOR,; PRAKASH PONNUDURAI SAMUEL GNANA, (International Journal of Pharma and Bio Sciences, 2017)
Periodontitis is an infectious ailment of multifactorial origin that brings about destruction of bone and surrounding tissues. The diagnosis of these periodontal diseases and identifying the patients who are at risk for these diseases always does possess a challenge for the clinicians. Ceruloplasmin is a ferroxidase enzyme that plays a role as an anti-inflammatory agent by its ability to scavenge free radicals within the body. Studies have compared the levels of serum ceruloplasmin in patients with Aggressive and Chronic Periodontitis with equivocal results. The aim of this study is to evaluate the level of serum Ceruloplasmin in Chronic Periodontitis patients with Type II Diabetes Mellitus and to compare it with gingivitis and systemically healthy Periodontitis patients. The study comprised a total of 40 subjects who were divided into four groups. The experimental groups consist of 10 subjects each in Gingivitis group, systemically healthy Chronic Periodontitis group and Chronic Periodontitis modified by Diabetes Mellitus group. The control group consisted of 10 healthy individuals free of periodontal diseases. Blood samples (5 ml) were collected from all the subjects using a vacutainer and following standard aseptic precautions. The samples were taken to the lab where the serum was extracted from the subjects’ blood by centrifugation. Spectroscopic analysis of the serum samples for detection of Ceruloplasmin levels were carried out. The clinical parameters showed statistically significant difference between the study groups which reflects the appropriate recruitment of subjects in each group. The serum levels of Ceruloplasmin were increased in the Periodontitis modified by Diabetes Mellitus group, although when analyzed statistically there were no significant differences between the study groups. The serum ceruloplasmin levels are slighty elevated in chronic periodontitis patients with diabetes mellitus.